Human Fcγ-receptors selectively respond to C-reactive protein isoforms - Henning, Anna; Seer, Johanna; Zeller, Johannes; Peter, Karlheinz; Chen, Haizhang; Thomé, Julia; Kolb, Philipp; Eisenhardt, Steffen U.; Hoffmann, Katja; Hengel, Hartmut (Frontiers in Immunology, 2025)
IntroductionThe pentameric C-reactive protein (pCRP), an acute-phase protein, binds to lysophosphatidylcholine (LPC) displayed on the surface of dying cells and microorganisms to activate the complement system and to opsonize immune cells via Fcγ-receptors (FcγRs). Members of the FcγR family are characterized by the recognition of the Fc part of IgG antibodies.MethodsWe utilized a mouse thymoma BW5147 reporter cell panel stably expressing chimeric human FcγR-CD3ζ-chain receptors to define the molecular requirements for FcγR crosslinking by C-reactive protein (CRP).ResultsApplying this approach, we show a robust activation of CD64/FcγRI and CD32a/FcγRIIa by immobilized CRP isoforms as well as triggering of inhibitory CD32b/FcγRIIb. Of note, activation of FcγRIIa was restricted to the 131R allelic variant but not observed with 131H. In contrast, FcγRIII isoforms CD16aF, CD16aV and CD16b were not activated by pCRP, although binding of CRP isoforms to FcγRIII was detectable. Activation of FcγRs by free pCRP in solution phase was considerably lower than with immobilized pCRP on hydrophilic plastic surfaces and readily abolished by IgG at serum level concentrations, whereas it was enhanced by the addition of streptococci. The types of FcγRs mainly responding to pCRP in solution phase (CD64/FcγRI and CD32aR/FcγRIIaR) clearly differed from FcγRs responding to soluble multimeric IgG complexes (i.e., CD16aV/FcγRIIIaV and CD32aH/FcγRIIaH). Compared to pCRP, monomeric CRP (mCRP) showed lower levels of activation in those selective FcγRs. FcγR activation was linked to recognition by conformation-dependent CRP antibodies. Unmasking of the mAb 9C9-defined neoepitope in pCRP* correlated with the triggering of FcγRs, indicating that pCRP* is the major FcγR-activating CRP conformation.DiscussionThe assay provides a novel, scalable approach to determine the molecular properties of CRP as a physiological ligand of FcγR-mediated bioactivities.